SPECIAL TASKS DIRECTED TO THE PERSON IN MOTHER TONGUE EDUCATION - Gulomova X.; Bakiyeva H. (Western European Studies, 2024)
The article talks about special assignments in mother tongue education
Keywords: Native language and literature; personality; orientation; special assignment